2021
DOI: 10.18388/abp.2020_5961
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D endocrine system in breast cancer

Abstract: Vitamin D is a steroid hormone of great importance in the human body. It is produced in the skin from 7-dehydrocholesterol, upon UV radiation. In order to exert its functions, vitamin D has to be hydroxylated (via CYP27A1 and CYP27B1 hydroxylases), which is followed by its interaction with the vitamin D receptor (VDR) or retinoic acid-related orphan receptors α or γ (RORα and RORγ). By binding with the vitamin D response elements (VDRE) located in the promoter regions, the vitamin D ligand-receptor complex may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 107 publications
(136 reference statements)
0
5
0
Order By: Relevance
“…However, only one study found a significant relationship between this polymorphism and OS. Heist et al report that in 294 patients of Caucasian origin (from USA) with advanced NSCLC, in the multivariate Cox regression model, patients carrying the CT and TT genotypes showed a higher risk of death than those carrying the CC genotype ( p = 0.04; HR = 1.32; 95% CI = 0.98–1.77; CT vs. CC, and p = 0.04; HR = 1.41; 95% CI = 0.96–2.07; TT vs. CC) [ 23 ]. The influence of FokI on PFS was assessed in three studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only one study found a significant relationship between this polymorphism and OS. Heist et al report that in 294 patients of Caucasian origin (from USA) with advanced NSCLC, in the multivariate Cox regression model, patients carrying the CT and TT genotypes showed a higher risk of death than those carrying the CC genotype ( p = 0.04; HR = 1.32; 95% CI = 0.98–1.77; CT vs. CC, and p = 0.04; HR = 1.41; 95% CI = 0.96–2.07; TT vs. CC) [ 23 ]. The influence of FokI on PFS was assessed in three studies.…”
Section: Resultsmentioning
confidence: 99%
“…These VDREs enable the expression of a host of genes, which are related to key processes in the inception and development of cancer. This evidence suggests that low serum calcidiol levels or dysfunctionality of the vitamin may favor carcinogenesis, due to the presence of single-nucleotide polymorphisms (SNPs) in the genes that participate in vitamin D metabolism ( GC or VDBP , VDR , CYP2R1 , CYP27B1 , and CYP24A1 ) [ 22 , 23 , 24 ]. There are studies that have evaluated the influence of SNP prevalence in these genes associated with risk, survival, progression-free survival, and response to platinum-based chemotherapy in lung cancer, specifically NSCLC [ 10 , 14 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The vitamin D receptor is commonly expressed in breast tissues, as well as in breast cancer cells [ 33 ]. It could be proven that vitamin D binds to vitamin D response elements of the promoter region of cells and thus regulates vitamin D-dependent genes [ 7 ]. A possible explanation of how vitamin D might affect breast cancer biology might be the tumor suppressive effects of vitamin D receptor catabolism, as a defect in the vitamin D receptor (e.g., CYP27B1 and CYP24A1 regulation) led to decreased signaling [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…By modulating IncRNA, vitamin D could have a protective effect on the development of breast cancer [ 34 ]. However, by now these results could mostly be shown in vitro and in animal experiments, not in clinical trials [ 7 , 8 , 9 ]. Thus, a general benefit of vitamin D substitution in cancer patients or influence on therapy success and outcome could not yet been proven [ 1 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation